Major initiative of ASHA Workers towards Maternal Health Care : A Urban Sociological Study - Dr.Urvashi Pandey • & Richa Tewari (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
India has made extensive efforts to reduce maternal mortality and to increase access to reproductive health care and in some regions much progress has been achieved. However many women still lack the access to maternal and reproductive health care due to the unstable and poor healthcare infrastructure. To overcome the difficulties of this inequitable healthcare infrastructure government of India launched the Accredited Social Health Activists (ASHA) programme as a part of the National Rural Health Mission (NHRM) in 2005. The ASHA workers provide basic maternal and child health care services along with the family planning services. The services of ASHA workers help in identifying the efficiencies and correcting the working pattern of their services with each patient right from registration to delivery of baby so that services through PHCs, CHCs & SHCs can easily be accessed. To address the role of ASHA worker in urban setting present study was conducted in Haldwani city of Nainital district (300 female respondents of reproductive age group). The data used in the study was analyzed using SPSS software 26.0 version. The findings of the study positively indicate the presence of ASHA workers during their pregnancy and respondents were fully satisfied with the working of ASHA workers in their area. Further significant association was found between role of ASHA workers and satisfaction level of respondents from the workings of ASHA workers in their area.